The Effect of Plyometric Training and Resistance on Movement Speed in Jombang Basketball Club Players - Nurdian Ahmad; Yudi Dwi Saputra (Universitas Majalengka, 2023)
Basketball is a team sport that requires optimal physique; many training models that improve physique include plyometrics and resistance. The purpose of this study was to determine the effect of plyometric training and resistance on movement speed in basketball club players. This type of research is quantitative research with experimental methods and designs using a pretest-posstest design. The subjects of this study consisted of 20 athletes who participated in training at the Jombang Basketball Club and would be given plyometric and resistance training treatments. Data analysis techniques in the study using the T test Based on the results of uji-t obtained in the group given plyometric training, the t count was 1.140 > 1.833, while in the resistance exercise group, the t count was 9.085 > 1,833. From the results of variables tied to each research group, it can be interpreted that there are differences between pre-test and post-test. Based on this study, it can be concluded that plyometric and resistance training have a significant influence on increasing the movement speed of basketball club players.